Kritik Epistemologi Metode Hermeneutika: Studi Kritis Terhadap Penggunaannya Dalam Penafsiran Al Quran - Fahimah, Siti (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2019)
Understanding of the Koran becomes a discipline that continues to experience development, as the development of the situation and conditions of the times, including the method of understanding the Koran or its interpretation. There are two big camps in the world of interpretation that can not be separated, namely first, the tradition that is used by Muslims or called traditionalists or conventional and interpretation traditions carried by modernists who carry a lot of Western methods. The traditionalists use a method that has been developed since the time of the Prophet to the present formulated by the interpretation of bil m'atsur in the Ijmali genre. Meanwhile, modern people use the hermeneutics method. In the development of the two traditions are often contested, one considered that the traditions of the tardisionalists are well established and do not need to be renewed by emphasizing the existing rules, while the hermeneutic method is an absurd method and cannot be accounted for even only assessing something that is relative. whatever the goals of the two traditions are clear they both have a goal that the Koran can be understood throughout the ages andsholih li kulli zaman wa makan.